Morphological and histochemical studies on the olfactory rosette of bagrid catfish, Rita kuturnee (Sykes, 1839) - Ghosh, S.K.; Chakrabarti, P. (Mesopotamian Journal of Marine Sciences, 2022)
In the present study, the functional anatomy, histological features and histochemical localization of two enzymes viz., alkaline phosphatase (ALPase) and adenosine triphosphatase (ATPase) of the olfactory epithelium in Rita kuturnee were described. The structural organization of the olfactory epithelium was studied by using the histological and histochemical techniques. The morpho-anatomical study revealed that the paired olfactory chambers were situated at the dorsal-lateral sides of the snout, which was communicated outside by an anterior and posterior nasal openings. The elongated olfactory rosette lied at the bottom of chamber and supported with 54-56 lamellae on either side of the central narrow raphe. The histological analysis characterized the olfactory epithelium of lamellae which was made up of receptor, flagellated supporting, non-flagellated supporting, labyrinth, mucous and basal cells. Intense alkaline phosphatase and adenosine triphosphatase activity were evidenced in the receptor cells, supporting cells, basal cells and also in blood cells of the central core. Various cells lining the olfactory epithelium were correlated with the functional significance of the fish was concerned.